Geopolitics of Global Leadership and Resource Competition in the Indo-Pacific: Implications for Indonesia's Defense Doctrine - Filianto Adiwibowo; Ilham Faisal Siregar; Tarsisius Susilo; Muhammad Taufiq Zega; Dudik Purwanto (International Research and Development for Human Beings (IRDH), 2025)
The geopolitical rivalry among the United States, China, and Russia in the Indo-Pacific region has intensified, particularly in the competition over strategic resources such as energy, critical minerals, maritime technology, and control of international trade routes. This dynamic poses direct implications for middle powers, including Indonesia, which occupies a pivotal position as a global maritime fulcrum. Such circumstances require Indonesia to adopt a defense doctrine that is not merely reactive to emerging threats but also proactive in fostering self-reliance and regional resilience. This article aims to analyze global leadership interactions in the Indo-Pacific context by employing transformational leadership theory (Burns, Bass), adaptive leadership (Heifetz), and military-strategic perspectives, while mapping Indonesia’s position through a SWOT analysis framework. The findings indicate that Indonesia possesses significant geopolitical strengths yet continues to face structural weaknesses, particularly in the modernization of defense systems and the self-sufficiency of its defense industry. Opportunities arise from multilateral cooperation and the development of renewable energy, whereas tangible threats stem from great-power rivalry and maritime security instability. These insights underscore the urgency of strengthening Indonesia’s defense doctrine in alignment with the Asta Cita vision, thereby safeguarding sovereignty, enhancing bargaining power, and ensuring Indonesia’s strategic role amid global rivalry.